Modelling of aero-elastic interactions of tall circular chimneys due to vortex-induced oscillations - Arunachalam, S. (Journal of Structural Engineering, 2024)
Research efforts are being continued for better understanding and modelling of lock-in phenomenon on circular chimneys due to vortex shedding, since the role of Reynolds number and turbulence intensity on various aerodynamic and aeroelastic parameters are not fully understood in the literature. In this summary paper, salient features of Vickery and Basu spectral model and Ruscheweyh correlation length model are briefly explained. Currently, these methods are widely recommended in international codes of practice on chimneys. Recent development by Lupi et al. on improving the aerodynamic damping in the spectral model, is also described and discussed. Further, details of development of a new semi-empirical model by the author, based on research study conducted at CSIR-SERC, and subsequently at JUET, Guna, are also presented which show a promising potential for prediction of across-wind response under lock-in condition. The method provides a closed-form solution which is useful and easy to adopt by the designers. Importance of application of machine learning based GBRT algorithms for wind engineering problems is highlighted.